Sound source localization in blind soccer: differences between sighted and visually impaired players - Watanabe, Masahiro (Journal of physical therapy science, 2024)
[Purpose] The sense of vision is omitted in blind soccer, and sound source localization to grasp the position of the ball is extremely important. The purpose of this study was to clarify whether there is a difference in ability in sound source localization in its approaching condition between visually impaired and sighted people, using the source actually used in blind soccer ball competitions. [Participants and Methods] Eighteen participants were divided into two groups; 10 sighted people and eight visually impaired people. The participants were asked to press a switch when a rolling blind soccer ball was sensed in any one of the four directions. We recorded time error as the difference between the time when the ball passed the optical sensor set under the participant's feet and when the participant pressed the switch. [Results] The time error in response increased with the ball speed in all cases; however, its dependence on the ball speed was significantly different between the two groups. [Conclusion] The visually impaired participants made less time errors in response to the localization of the ball than the sighted participants, even when the ball speed increased. The results indicate that visually impaired people have better sound source localization ability than sighted people do.